Pelvic floor and abdominal muscle cocontraction in women with and without pelvic floor dysfunction: A systematic review and meta-analysis - Vesentini, Giovana [UNESP]; El Dib, Regina [UNESP]; Righesso, Leonardo Augusto Rachele; Piculo, Fernanda [UNESP]; Marini, Gabriela [UNESP]; Ferraz, Guilherme Augusto Rago [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Elsevier, 2019)
There is an ongoing discussion regarding abdominal muscle (AbM) and pelvic floor muscle (PFM) synergism. Therefore, this study aimed to investigate the cocontraction between AbMs and PFMs in women with or without pelvic floor dysfunction (PFD). The following databases were searched up to December 21, 2018: MEDLINE, EMBASE, LILACS, PEDro and CENTRAL. We included any study that assessed the cocontraction between PFMs and AbMs in women with and without PFD. Two reviewers independently screened eligible articles and extracted data. The outcomes were extracted and analyzed as continuous variables with random effect models. Twenty studies were included. A meta-analysis did not show differences in women with and without PFD. However, a sensitivity analysis suggested cocontraction of the transversus abdominis (TrA) during PFM contraction in healthy women (standardized mean difference (SMD) 1.02 [95% confidence interval (CI) 1.90 to 0.14], P=0.02; I2= not applicable; very low quality of evidence). Women with PFD during contraction of PFMs showed cocontraction of the obliquus internus (OI) (SMD 1.10 [95% CI 0.27 to 1.94], P=0.01; I2= not applicable; very low quality of evidence), and obliquus externus (OE) (SMD 2.08 [95% CI 1.10 to 3.06], Po0.0001; I2 = not applicable; very low quality of evidence). Increased cocontraction of the TrA may be associated with maximal contraction of PFMs in women without PFD. On the other hand, there is likely an increased cocontraction with the OI and OE in women with PFD.
Keywords: Abdominopelvic Muscles; Pelvic Floor Disorders; Pelvic Floor Function; Synergism